Ultrasonic atomization of tissue and its role in tissue fractionation by high intensity focused ultrasound - Simon, Julianna C. (2012)
Atomization and fountain formation is a well-known phenomenon that occurs when a focused ultrasound wave in liquid encounters an air interface. High intensity focused ultrasound (HIFU) has been shown to fractionate tissue into submicron-size fragments in a process termed boiling histotripsy, wherein the focused ultrasound wave superheats the tissue at the focus, producing a millimetre-size boiling or vapour bubble in several milliseconds. Yet the question of how this millimetre-size boiling bubble creates submicron-size tissue fragments remains. The hypothesis of this work is that tissue can behave as a liquid such that it forms a fountain and atomization within the vapour bubble produced in boiling histotripsy. We describe an experiment, in which a 2-MHz HIFU transducer (maximum in situ intensity of 24,000 W/cm(2)) was aligned with an air-tissue interface meant to simulate the boiling bubble. Atomization and fountain formation were observed with high-speed photography and resulted in tissue erosion. Histological examination of the atomized tissue showed whole and fragmented cells and nuclei. Air-liquid interfaces were also filmed. Our conclusion was that HIFU can fountain and atomize tissue. Although this process does not entirely mimic what was observed in liquids, it does explain many aspects of tissue fractionation in boiling histotripsy.